A Study to Assess the Internet Addition and Social Withdrawal Among Students of Private Institute of Block Pacchad, Distt. Sirmour, H.P. - Sameeksha; Sharma, Upasna; Mehta, Yati; Tamana; Vasundhra; Vaishali (International Journal of Nursing Education)
Background: Internet addiction is one of the socially growing issues. It has been affecting large number of population mainly the youth. Internet has become essential part of our daily life mainly among students, adolescents and youth. The study aims to find out the correlation between internet addiction and loneliness. Methods: Correlation study design was used for the conduction of study. By using total enumerative sampling 98 samples were selected. Internet addiction and UCLA loneliness scale were used for data collection. Study results revealed that most of sample were of 21years and 52% study samples were UG students. 41.8% of the students having family income between 2.5 to 5 lakh. 41.8% of the students use their phone for 2-4 hours per day and mostly 77.6% spending time on social networking applications. 86.7% samples spent 500-700Rs for monthly data packs. 46.9% samples reported that they had satisfactory relationship with their family members. 70.0% of the students often feel stressed for not being able to use internet for couple of hours. Conclusion: Study results showed that there was correlation between internet addictions and loneliness. This study conclude that that internet addiction does not lead to loneliness.